Kết quả đánh giá độ trễ thiên đỉnh và hàm lượng hơi nước tổng cộng tầng đối lưu từ số liệu GPS ở Việt Nam - Minh, Lê Huy; Masson, Frédéric; Duchesne, P. Lassudrie; Bourdillon, A.; Lan, Trần Thị; Thành, Phạm Xuân; Thắng, Nguyễn Chiến; Nam, Trần Ngọc; Lan, Hoàng Thái (Vietnam Journal of Earth Sciences, 2009)
Preliminary results of the estimation of the zenith total delay and the integrated water vapour of the troposphere by GPS data in Vietnam ...